2008
DOI: 10.1073/pnas.0810475105
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gene targeting in Drosophila by direct embryo injection with zinc-finger nucleases

Abstract: We report very high gene targeting frequencies in Drosophila by direct embryo injection of mRNAs encoding specific zinc-finger nucleases (ZFNs). Both local mutagenesis via nonhomologous end joining (NHEJ) and targeted gene replacement via homologous recombination (HR) have been achieved in up to 10% of all targets at a given locus. In embryos that are wild type for DNA repair, the products are dominated by NHEJ mutations. In recipients deficient in the NHEJ component, DNA ligase IV, the majority of products ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
254
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(270 citation statements)
references
References 52 publications
11
254
3
2
Order By: Relevance
“…These findings indicate that spontaneous homologous recombination is a rare event in the sea urchin embryo and that a ZFN-induced DSB at the target site stimulates HDR, resulting in the induction of targeted transgene insertion at a detectable level. This result is in agreement with earlier work using Drosophila and mice (7,14), suggesting that ZFN-mediated targeted insertion is feasible in model animals, although the efficiency of the insertion may depend on the species. Addition of ZFN target sites at both ends of the targeting donor cassette significantly increased the efficiency of ZFN-mediated targeted transgene insertion.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings indicate that spontaneous homologous recombination is a rare event in the sea urchin embryo and that a ZFN-induced DSB at the target site stimulates HDR, resulting in the induction of targeted transgene insertion at a detectable level. This result is in agreement with earlier work using Drosophila and mice (7,14), suggesting that ZFN-mediated targeted insertion is feasible in model animals, although the efficiency of the insertion may depend on the species. Addition of ZFN target sites at both ends of the targeting donor cassette significantly increased the efficiency of ZFN-mediated targeted transgene insertion.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that DNA ligase IV, a major component of the NHEJ pathway, forms a complex with XRCC4 and seals DNA ends (22). Moreover, DSB repair can be biased toward HDR by disrupting the function of DNA ligase IV, resulting in an increase in the efficiency of targeted gene modification (7). Therefore, we hypothesized that in the sea urchin, inhibition of DNA ligase IV through the introduction of DN-lig4 mRNA increases the propensity to repair ZFN-induced DSBs through HDR, resulting in enhanced efficiency of ZFN-mediated targeted transgene insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter approach ensures that DNA is cleaved only when ZFNs for the left and right halfsites are positioned at the appropriate target sequence on the chromosome. Limited expression of ZFNs either by transient DNA delivery, injected RNA, or inducible expression systems has also been suggested as a strategy to reduce undesired toxic effects (32,33,36).…”
Section: Discussionmentioning
confidence: 99%
“…A y w stock was used as control. Two coilin null lines, coil 199 and coil 203 , were generated by site-specific mutation using zincfinger nucleases (Beumer et al, 2008;Liu et al, 2009). Drosophila S2 cells were used as an additional wild-type control.…”
Section: Fliesmentioning
confidence: 99%